1997
DOI: 10.1111/j.1439-0396.1997.tb00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between proline balance in the rat kidney and intrarenal concentration of amino acids

Abstract: Summary In the present study, a proline‐deficient diet was fed to rats in order to reduce the plasma proline concentration to that observed during fasting and then the carotid‐artery‐renal‐vein differences in various amino acids and intrarenal amino acid concentrations were measured in order to investigate the kinetics of amino acid metabolism in the kidney. The plasma proline concentration in the carotid arteries of the proline‐deficient diet group 8 h after the beginning of the last feed was significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Interestingly, the kidney is a hub for arginine/proline biosynthesis, which likely increases local concentrations of arginine/proline that contribute to rapid filamentation in C . albicans [ 60 62 ]. Two-photon microscopy has previously been used to image fungal infections in translucent mouse pinna (ears) [ 90 ], however, to our knowledge, our studies represent the first in which C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the kidney is a hub for arginine/proline biosynthesis, which likely increases local concentrations of arginine/proline that contribute to rapid filamentation in C . albicans [ 60 62 ]. Two-photon microscopy has previously been used to image fungal infections in translucent mouse pinna (ears) [ 90 ], however, to our knowledge, our studies represent the first in which C .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that compared to other organs, C. albicans filament faster in the kidney suggesting the presence of kidney-specific cues. Interestingly, the kidney is a hub for arginine/proline biosynthesis, which likely increases local concentrations of arginine/proline that contribute to rapid filamentation in C. albicans [60][61][62]. Two-photon microscopy has previously been used to image fungal infections in translucent mouse pinna (ears) [90], however, to our knowledge, our studies represent the first in which C. albicans infections have been imaged under physiological in situ conditions in a complex intravital organ (Fig 6).…”
Section: Plos Pathogensmentioning
confidence: 94%
See 1 more Smart Citation
“…While proline and Pycr1 regulation has been linked to Atf4 signalling previously, this was in the context of stem cell differentiation (D'Aniello et al, 2015) and not that of mitochondrial dysfunction. Although it has been suggested that the pancreas is the major site of proline production in vivo (Tran et al, 2021), the kidney has been proposed to operate as a proline-producing organ under conditions of fasting and with low proline diets (Watanabe et al, 1999;Watanabe et al, 1997). Given the high density of mitochondria in proximal kidney tubules, it would be tempting to speculate that high rates of oxidative TCA activity could be important to facilitate proline biosynthesis for use by other organs under conditions of fasting or nutrient scarcity.…”
Section: Discussionmentioning
confidence: 99%